2012
DOI: 10.1128/jvi.07139-11
|View full text |Cite
|
Sign up to set email alerts
|

Selection Pressure on HIV-1 Envelope by Broadly Neutralizing Antibodies to the Conserved CD4-Binding Site

Abstract: The monoclonal antibody (MAb) VRC01 was isolated from a slowly progressing HIV-1-infected donor and was shown to neutralize diverse HIV-1 strains by binding to the conserved CD4 binding site (CD4bs) of gp120. To better understand the virologic factors associated with such antibody development, we characterized HIV-1 envelope (Env) variants from this donor and five other donors who developed broadly neutralizing antibodies. A total of 473 env sequences were obtained by single-genome ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 84 publications
5
92
1
Order By: Relevance
“…Thus, production of less effective almost PVL Abs such as 3BNC55 may be selected in HIV-infected patients in response to evolution of viruses such as T250-4 that are resistant to PVL Abs. A similar in vivo selection scenario has been proposed for VRC03 and VRC06 (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, production of less effective almost PVL Abs such as 3BNC55 may be selected in HIV-infected patients in response to evolution of viruses such as T250-4 that are resistant to PVL Abs. A similar in vivo selection scenario has been proposed for VRC03 and VRC06 (27).…”
Section: Resultsmentioning
confidence: 99%
“…We also examined sequences for HIV envelopes isolated from donor 45 (from whom VRC01, VRC03, and NIH45-46 were isolated) (20,23), including 3 early proviral clones sensitive to VRC01 and 26 later clones that were insensitive to VRC01, plus additional Env clones from other individuals with strongly HIV-1-neutralizing sera (27). Variation at the critical gp120 sites (279 gp120 , 280 gp120 , 456 gp120 , 458 gp120 , and 459 gp120 ) correctly predicted sensitivity to PVL Abs for all 29 gp120 sequences from donor 45 (Fig.…”
Section: G54wmentioning
confidence: 99%
“…Therefore, the observed variation in SIVsmm more likely results from gradual accrual of mutations over time (i.e., genetic drift) than from rapid selection for immune evasion. In contrast, rapid immune escape is a major aspect of positive selection in HIV-1: most early mutations are concentrated within T cell epitopes (17,18,25,27), viruses within individuals continually evolve to escape from neutralizing antibodies during chronic infection (3,61,91), and HLA imprinting is evident in viruses circulating in different human populations (37,67).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies on individuals with broadly cross-neutralizing Abs showed that these individuals had higher viral loads and that the breadth of NAbs did not affect disease progression (12,15,46), confounding a clear role for NAbs in preventing viral pathogenesis. Indeed, escape from neutralization was also observed in individuals from whom highly potent broadly cross-neutralizing antibodies were derived (7,8,65). Since clinical outcome and disease progression in HIV infection are affected by many other factors, such as host genetics, diversity of the infecting virus, and difference in routes of infection, it is difficult to evaluate the effect of NAbs on HIV-1 disease progression in such clinical studies.…”
mentioning
confidence: 99%